The relationship between student's perceptions of the learning environment with learning outcomes of the immune system in distance learning - Cahyati, Fitria Nur; Miarsyah, Mieke; Rahayu , Sri (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Students' perception of the learning environment is the process of students interpreting the learning experiences they receive. The learning environment is an external factor that has an important role in the learning process, to facilitate students and teachers in achieving learning goals. This study aims to determine the relationship between student's perceptions of the learning environment with learning outcomes of the immune system in distance learning. This research was conducted at State Senior High School 21 Jakarta in June of 2020/2021. The method used was quantitative with a correlational study. The sample in this study was 105 students of second grade class by simple random sampling. The research instrument using the Dundee Ready Education Environment Measure (DREEM) questionnaire with a measurement scale, namely the Likert scale. The learning outcome instrument using test based on basic competence and competency achievement indicators (GPA). The test is in the form of multiple choice with five answer choices. The prerequisite Test shows the data is normally distributed and homogeneous. Based on the statistical hypothesis testing results, a significant regression model and the correlation coefficient have a strong relationship. Furthermore, the students' perceptions of the learning environment were related to the learning outcomes of the immune system in distance learning